CONFORMANCE ASSESSMENT WITH THE WEB CONTENT ACCESSIBILITY GUIDELINES (WCAG) - Edson Rufino de Souza; Cláudia Mont’Alvão (Ergodesign & HCI, 2018)
This article aims to present steps of a research that studied the relationship between an accessibility assessment technique – the verification of website compliance with WCAG 2.0 – with the characteristics of the profile of the evaluator. To this end, two exploratory studies were preliminarily carried out: first, with different profiles of expertise and predetermined script; and second, with high level of expertise and free script, with only the technique to be used being predefined. The studies indicated (1) the confirmation of a high relation of a profile more adherent to the knowledge about accessibility and web technologies with the results of the evaluation and (2) the possibility of misinterpretations of the application of a technique without presetting all the steps to be followed. From this, with a predefined itinerary based on the document WCAG-EM 1.0, a third study was done, only with volunteers evaluators with adequate level of knowledge and experience related to accessibility, recruited through an online questionnaire. There were 83 respondents, with 62 valid answers and 25 fulfilled the criteria to be considered fit for the accessibility evaluation stage. Among these, nine volunteers performed individual evaluations by the technique studied according to the predefined itinerary, and the results were compared to each other. There were many inconsistencies in understanding and in the way of reporting the problems, with one of the evaluators who had a better self-assessment compared to the others. The results confirmed the importance of the evaluator profile for the effectiveness of the conformance verification technique.